It takes two to tango: Widening our understanding of the onset of schizophrenia from a neuro-angiogenic perspective - Casas, Bárbara S.; Arancibia-Altamirano, David; Acevedo-La Rosa, Franco; Garrido-Jara, Delia; Maksaev, Vera; Pérez-Monje, Dan; Palma, Verónica (Frontiers in Cell and Developmental Biology, 2022)
Schizophrenia is a chronic debilitating mental disorder characterized by perturbations in thinking, perception, and behavior, along with brain connectivity deficiencies, neurotransmitter dysfunctions, and loss of gray brain matter. To date, schizophrenia has no cure and pharmacological treatments are only partially efficacious, with about 30% of patients describing little to no improvement after treatment. As in most neurological disorders, the main descriptions of schizophrenia physiopathology have been focused on neural network deficiencies. However, to sustain proper neural activity in the brain, another, no less important network is operating: the vast, complex and fascinating vascular network. Increasing research has characterized schizophrenia as a systemic disease where vascular involvement is important. Several neuro-angiogenic pathway disturbances have been related to schizophrenia. Alterations, ranging from genetic polymorphisms, mRNA, and protein alterations to microRNA and abnormal metabolite processing, have been evaluated in plasma, post-mortem brain, animal models, and patient-derived induced pluripotent stem cell (hiPSC) models. During embryonic brain development, the coordinated formation of blood vessels parallels neuro/gliogenesis and results in the structuration of the neurovascular niche, which brings together physical and molecular signals from both systems conforming to the Blood-Brain barrier. In this review, we offer an upfront perspective on distinctive angiogenic and neurogenic signaling pathways that might be involved in the biological causality of schizophrenia. We analyze the role of pivotal angiogenic-related pathways such as VEGF and HIF signaling related to hypoxia and oxidative stress events; classic developmental pathways such as the NOTCH pathway, metabolic pathways such as the mTOR/AKT cascade; emerging neuroinflammation, and neurodegenerative processes such as UPR, and also discuss non-canonic angiogenic/axonal guidance factor signaling. Considering that all of the mentioned above pathways converge at the Blood-Brain barrier, reported neurovascular alterations could have deleterious repercussions on overall brain functioning in schizophrenia.